Expression of the Arabidopsis thaliana immune receptor EFR in Medicago truncatula reduces infection by a root pathogenic bacterium, but not nitrogen‐fixing rhizobial symbiosis. Issue 3 (13th September 2018) - Pfeilmeier, Sebastian; George, Jeoffrey; Morel, Arry; Roy, Sonali; Smoker, Matthew; Stransfeld, Lena; Downie, J. Allan; Peeters, Nemo; Malone, Jacob G.; Zipfel, Cyril
Summary: Interfamily transfer of plant pattern recognition receptors (PRRs) represents a promising biotechnological approach to engineer broad‐spectrum, and potentially durable, disease resistance in crops. It is however unclear whether new recognition specificities to given pathogen‐associated molecular patterns (PAMPs) affect the interaction of the recipient plant with beneficial microbes. To test this in a direct reductionist approach, we transferred the Brassicaceae ‐specific PRR ELONGATION FACTOR‐THERMO UNSTABLE RECEPTOR (EFR), conferring recognition of the bacterial EF‐Tu protein, from Arabidopsis thaliana to the legume Medicago truncatula . Constitutive EFR expression led to EFR accumulation and activation of immune responses upon treatment with the EF‐Tu‐derived elf18 peptide in leaves and roots. The interaction of M. truncatula with the bacterial symbiont Sinorhizobium meliloti is characterized by the formation of root nodules that fix atmospheric nitrogen. Although nodule numbers were slightly reduced at an early stage of the infection in EFR ‐ Medicago when compared to control lines, nodulation was similar in all lines at later stages. Furthermore, nodule colonization by rhizobia, and nitrogen fixation were not compromised by EFR expression. Importantly, the M. truncatula lines expressing EFR were substantially more resistant to the root bacterial pathogen Ralstonia solanacearum . Our data suggest that the transfer of EFR to M. truncatula does not impede root nodule symbiosis, but has a positive impact on disease resistance against a bacterial pathogen. In addition, our results indicate that Rhizobium can either avoid PAMP recognition during the infection process, or is able to actively suppress immune signaling.